Ethnic and political myths as a factor of forming the public opinion - Asriyan, Elina (Przegląd Wschodnioeuropejski, 2017)
The word ‘myth’ means tradition, legend. Myth-making is seen as the most important event in the cultural history of mankind. In primitive society mythology presents the basic way of understanding the world. The history of the people needs to be told of his mythology, and not vice versa. In our view when creating the image of a political leader should come from the heroic myths. The main characteristics of political myth are relying on the archetype and some technological artifice. We can say that the political myth is an adaptation of a cultural myth for political purposes. Political myth thus becomes a necessary form of communication between people and the government. Political myths are widely used in election campaigns, because from a psychological point of view the mythologizing the political leader allows differentiate him from competitors.